SerumTrace Elements in Febrile Seizure: A Case-Control Study - NAMAKIN, Kokab; ZARDAST, Mahmoud; SHARIFZADEH, Gholamreza; ZARGARIAN, Toktam; BIDAR, Samaneh (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Namakin K, Zardast M, Sharifzadeh Gh, Bidar T, Zargarian S. Serum Trace Elements in Febrile Seizure: A Case-Control Study. Iran J Child Neurol. Summer 2016; 10(3):57-60. Abstract Objective Febrile seizure (FS) is one of the most common neurological problems during childhood.Pathogenesis of febrile convulsion is unknown. This study investigated some trace elements among children admitted with FS compared with thoseof febrile without seizure attacks. Materials & Methods This case-control study was conducted on48 children (6 months to 5 yr old) diagnosed with febrile seizure as the cases and 48 age-matched febrile children as the control group. Serum levels of magnesium, calcium, sodium, potassium, and serum zinc were measured. Statistical analysis was performed with SPSS (version 15) using Student t-test. Results There were no significant differences between the cases and controls in terms of gender or age. The means of serum level of zinc, sodium, calcium and magnesium in the case group was lower than those of the control group. There was no significant difference onserum potassium mean level between the case and control groups. Conclusion Deficiency of trace elements was correlated significantly with febrile convulsion, while further investigations on trace elements are required. <span style="font-family: 'Times New Roman','serif'; mso-ascii-theme-font: major-bidi; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi;">References References Martindale JL, Goldstein JN, Pallin DJ. Emergency department seizureepidemiology. Emerg Med Clin North Am 2011;29:15-27. Lee J-H, Hyun Kim J.Comparison of Serum Zinc Levels Measured by Inductively Coupled Plasma Mass Spectrometry in Preschool Children with Febrile and Afebrile Seizures. Ann Lab Med 2012;32:190-193 http://dx.doi.org/10.3343/alm.2012.32.3.190. Akbayram S, Cemek M, Büyükben A, Aymelek F, Karaman S, Yilmaz F, Dogan M,Caksen H. Major and minor bio-element status in children with febrile seizure. Bratisl Lek Listy 2012; 113 (7)421 – 423. Johnston MV. Seizures in children. In: Behrman RE, JensonHB, Stanton BF, editors. Nelson Textbook of Pediatrics.18thed. Philadelphia: Saunders, 2008:2457-73. Salehiomran MR, Mahzari M. Zinc status in febrile seizure: a case-control study. Iran J Child Neurol 2013; 7(4):20-23. Nadkarni J, Binaykiya I, Sharma U, Dwivedi R. Role of serum sodium levels in prediction of seizure recurrence within the same febrile illness.Neurology Asia 2011; 16(3): 195–197. Ganesh R, Janakiraman L. Serum zinc levels in children with simple febrile seizure. Clin Pediatr (Phila) 2008;47:164–166. Waqar Rabbani M, Ali I, Zahid Latif H, Basit A, Rabbani MA. Serum zinc level in children presenting with febrile seizures. Pak J Med Sci 2013;29(4):1008-11. Ehsanipour F, Talebi-Taher M, Harandi N, Kani K. Serumzinc level in children with febrile convulsion and itscomparison with that of control group. Iran J Pediatr2009;65-8. Amiri M, Farzin L, Moassesi ME, Sajadi F. Serum trace element levels in febrile convulsion. Biol Trace Elem Res 2010;135(1-3):38-44. Mohamed Aly IAR, Mohamed Kmal H, Soliman DR, Hassan Mohamed M. Iron profile parameters and serum zinc & copper levels in children with febrile convulsions in Banha. J Am Sci 2014;10(7): 1-4. Gattoo I, Harish R, Quyoom Hussain S. Correlation of serum zinc level with simple febrile seizures: a hospital based prospective case control study. Int J Pediatr 2015;3(2):16-.19. Sadeghzadeh M, Nabi S, Khoshnevisasl P, Mousavinasab N. The correlation between cerebrospinal fluid and levels of serum zinc and Ca in children with febrile seizure. J Comprehens Pediatr 2013; 3(5): 179-83. Osama N. Salah, Ehab R. Abdelraou, Marwa H. Abdelhameed Ahmed A, Dawood, Adel F,Kilany HA, Suzette I. Assessment of the Level of GABA and some trace elements in blood in children who suffer from familial febrile convulsions. Macedonian JMed Sci 2014; 7(1):68-73. Heydarian F, Ashrafzadeh F, Cam S. Simple febrile seizure: the role of serum sodium levels in prediction of seizure recurrence during thefirst 24 hours. Iran J Child Neurol2009; 3(2):31-4.